(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Inflammation is a highly dynamic process. After just 4 hours, changes begin to occur in the inflammatory infiltrate and vascular bed: the number of neutrophils decreases and the number of mononuclear cells, mainly monocytes and lymphocytes, increases. These changes correlate with a change in the phenotype of adhesive molecules expressed by endothelial cells.